(untitled) (College of Basic Education Research Journal, 2025)
The aim of this study was to identify the values ​​of some types of kinematic balls (high hand throw speed, angle of the racket, height of the impact point, level of impact level, level of the racket level, level of the ball’s first impact distance with the table, height of the ball from the table, and speed of the ball’s rise from the table) for the performance of the forehand serve according to outstanding performance. This study also aimed to determine the extent of forehand skill from the new research, and to understand the meaning of the relationship between some of the research kinematic variables and outstanding performance of the forehand serve skill in long tennis. In order to conduct the study, the researcher selected players from the College of Basic Education team in table tennis. They were photographed with a fast camera, and then the kinetic analysis of the players’ performance was conducted using a special computer analysis program designed by (Al-Hayali, 2023, 45) to obtain the values ​​of the research variables, which were entered into the (SPSS) program with the performance accuracy test scores in order to obtain a significant degree of the relationship between the kinematic variables and the accuracy of the performance of the forehand serve skill in table tennis. The researcher concluded that the height of the ball throw (H1) affected the accuracy of the forehand serve of one of the research sample members. In addition, the values of the kinematic variables (S1, S3, A2, A3) differed between the performance of the research sample and the performance model of the forehand serve skill of the coach.